The Effect of Health Anxiety on Subjective Happiness: Does Optimism Play a Protective Role? - Feridun Kaya; Gulin Yazici-Celebi; Muge Yilmaz (Journal of Education in Science, Environment and Health)
In this study, health anxiety and optimism were determined as predictors of subjective happiness. A total of 301 individuals, 168 females (55.8%) and 133 males (44.2%) participated in the study carried out based on the correlational model. The research data were collected online due to the pandemic. In the study, Personal Information Form, Health Anxiety Scale, Optimism Scale and Subjective Happiness Scale were used as data collection tools. According to the findings obtained from the study, statistically significant and negative correlations were found between the health anxiety variable and the variables of subjective happiness and optimism. In addition to these results, statistically significant and positive correlations were determined between the optimism variable and subjective happiness variable. Mediation analyses were conducted in the study, and according to the results, it was revealed that optimism had a mediating role in the relationship between health anxiety and subjective happiness. As a result, the indirect effect of health anxiety on subjective happiness was found to be statistically significant. It is believed that the findings of the research will benefit experts who prepare intervention programs for individuals who experience intense anxiety during the pandemic process and who have low levels of subjective happiness.